Coccolithophore populations and their contribution to carbonate export during an annual cycle in the Australian sector of the Antarctic zone - Rigual Hernández, Andrés Salvador; Flores Villarejo, José Abel; Sierro Sánchez, Francisco Javier; Fuertes Prieto, Miguel Ángel; Cros, Lluïsa; Trull, Thomas W. (Biogeosciences, 2018)
[EN]he Southern Ocean is experiencing rapid and relentless change in its physical and biogeochemical properties. The rate of warming of the Antarctic Circumpolar Current exceeds that of the global ocean, and the enhanced uptake of carbon dioxide is causing basin-wide ocean acidification. Observational data suggest that these changes are influencing the distribution and composition of pelagic plankton communities. Long-term and annual field observations on key environmental variables and organisms are a critical basis for predicting changes in Southern Ocean ecosystems. These observations are particularly needed, since high-latitude systems have been projected to experience the most severe impacts of ocean acidification and invasions of allochthonous species. Coccolithophores are the most prolific calcium-carbonate-producing phytoplankton group playing an important role in Southern Ocean biogeochemical cycles. Satellite imagery has revealed elevated particulate inorganic carbon concentrations near the major circumpolar fronts of the Southern Ocean that can be attributed to the coccolithophore Emiliania huxleyi. Recent studies have suggested changes during the last decades in the distribution and abundance of Southern Ocean coccolithophores. However, due to limited field observations, the distribution, diversity and state of coccolithophore populations in the Southern Ocean remain poorly characterised. We report here on seasonal variations in the abundance and composition of coccolithophore assemblages collected by two moored sediment traps deployed at the Antarctic zone south of Australia (2000 and 3700 m of depth) for 1 year in 2001–2002. Additionally, seasonal changes in coccolith weights of E. huxleyi populations were estimated using circularly polarised micrographs analysed with C-Calcita software. Our findings indicate that (1) coccolithophore sinking assemblages were nearly monospecific for E. huxleyi morphotype B/C in the Antarctic zone waters in 2001–2002; (2) coccoliths captured by the traps experienced weight and length reduction during summer (December–February); (3) the estimated annual coccolith weight of E. huxleyi at both sediment traps (2.11 ± 0.96 and 2.13 ± 0.91 pg at 2000 and 3700 m) was consistent with previous studies for morphotype B/C in other Southern Ocean settings (Scotia Sea and Patagonian shelf); and (4) coccolithophores accounted for approximately 2–5 % of the annual deep-ocean CaCO3 flux. Our results are the first annual record of coccolithophore abundance, composition and degree of calcification in the Antarctic zone. They provide a baseline against which to monitor coccolithophore responses to changes in the environmental conditions expected for this region in coming decades. European Union's Horizon 2020, Marie Skłodowska-Curie Individual fellowship